From Unstructured Data to Insights: Understanding the Role of ChatGPT in the Rising Trend of AI Chatbots in Web Publications - Milev, Plamen; Tabov, Yavor (UNWE Yearbook, 2024)
In this research, we delve into the expanding presence of AI chatbots in online media. Leveraging data mining and natural language processing, we dissected unstructured data from web publications to track the trajectory of chatbot popularity, focusing on OpenAI’s ChatGPT. Our findings reveal a pronounced uptrend in AI chatbot integration and user interaction, with ChatGPT emerging as a pivotal figure. This uptick indicates a broader acceptance and integration of AI in digital interactions. The study underscores the pivotal role of ChatGPT in shaping user experience and offers foresight into future AI chatbot applications in the digital media realm.
Keywords: Chat GPT; AI; Chatbots; Unstructured data; Web publications; Trend analysis